Identifikasi Jenis Bivalvia yang Hidup pada Kawasan Hutan Mangrove Desa Tongke-Tongke Kabupaten Sinjai - Wahyuni, Andi Lis; Nurhaliza; Sumra (Jurnal Riset Diwa Bahari (JRDB), 2024)
Identification of Bivalvia Types that live in the mangrove forest area of Tongke-tongke village, East Sinjai District, Sinjai Regency. This research aims to identify the types of bivalves that live in the Tongke-tongke Mangrove Forest Area. This research was carried out from November to December 2023. The sampling stations were divided into 3 locations. Sampling used the line transect technique which is the benchmark for placing plots measuring 1 m x 1 m. The bivalves found in the plot are the samples for observation. Phenotypic for all types of bivalves found were matched with identification books and data on internet sites about seawater mollusks, so there is little possibility of errors in determining the type (species) of bivalves found in the Tongke-tongke mangrove forest area. From the results of the research, 4 types of species were found, including 37 tahu clams (Meretrix meretrix), 8 lokan clams (Geloina erosa), 42 darah clams (Anadara granosa), and 31 bulu clams (Anadara antiquate), so The total number of shellfish (bivalves) found was 118 individuals